DIAGNOSTIC ACCURACY OF MAGNETIC RESONANCE IMAGING (MRI) FOR MENISCAL KNEE INJURIES TAKING ARTHROSCOPY AS THE GOLD STANDARD - SAJID , M; UPPAL , MSK; BAJWA , ZU; TAHSEEN , R (Biological and Clinical Sciences Research Journal, 2023)
The accurate non-invasive diagnosis of meniscal tears is challenging. Magnetic resonance imaging (MRI) is commonly employed, but previous studies have reported inconsistent findings regarding its diagnostic accuracy. This study aimed to determine the diagnostic accuracy of MRI for detecting meniscal injuries in the knee joint using arthroscopy as the gold standard. The cross-sectional study was conducted at the Department of Orthopedics, Jinnah Hospital Lahore, from October 17, 2021, to April 16, 2022. Ethical approval was obtained from the hospital's Ethical Review Board, and all eligible patients were enrolled after providing informed consent. MRI scans were performed on all patients to assess meniscal injuries, followed by arthroscopy performed by a consultant Orthopedic Surgeon in the department. The collected data were analyzed using SPSS version 20. 131 patients were included in the study, with a mean age of 35.06 ± 8.32 years. The majority of the patients were male (79.4%). The mean body mass index (BMI) was 23.37 ± 4.05 kg/m², and the mean duration of illness was 5.20 ± 2.6 months. The sensitivity and specificity of MRI for diagnosing medial meniscal injuries were found to be 77.4% and 44.9%, respectively. For lateral meniscal injuries, the specificity was 66.7%, and the specificity was 65.3%. MRI demonstrated good sensitivity in detecting meniscal injuries when arthroscopy findings were considered the gold standard. However, its specificity was low for detecting these lesions. Therefore, MRI may be used as a screening tool for these patients, but arthroscopy remains the gold standard for definitive diagnosis.